Vers une analyse de l'apprentissage des langues en environnements virtuels immersifs - Hani Qotb (Corela)
Language immersion is one of the didactic approaches that enable individuals to learn a foreign language. Owing to development in Information and Communication Technologies (ICT), Immersive Virtual Environments (IVE) have emerged, and these make online language courses possible. With Hymes’ (1984) SPEAKING model, we analyse the different components of immersive Internet language training focusing on the following points: settings, participants, aims, language acts, tonality, instrumentality, norms and genders. Taking into account these elements facilitates the understanding of immersive Internet learning while helping instructors improve scenarising language courses within IVE so as to achieve learning goals